Институциональный потенциал промышленных регионов Украины - Солдак, М.А. (Економіка промисловості, 2014)
Решение задачи определения потенциала региона дополнено разработкой новых подходов к определению сущности, структур и методов оценки институционального потенциала. Предложены группы показателей для оценки институционального потенциала. Определены особенности институционального потенциала промышленных регионов Украины, что указывает на нецелесообразность формирования и внедрения единой политики регионального развития. Вирішення завдання визначення потенціалу регіону доповнено розробкою нових підходів до визначення сутності, структур та методів оцінки інституційного потенціалу. Запропоновано групи показників для оцінки інституціонального потенціалу. Визначено особливості інституційного потенціалу промислових регіонів України, що вказує на недоцільність формування та впровадження єдиної політики регіонального розвитку. In the modern economic science the solution of such task as the diagnostics of region’s potential should be supplemented by the assessment of the institutional potential since the impact of the institutes on the economic activity as incentives and constraints for individuals is well recognized. The aim of the article is to elaborate new approaches to the identification of the essence, structures and methods of assessment of region’s institutional potential, as well as of features of industrial regions’ institutional potential. To systematize the indicators characterizing the level of region’s institutional potential the concept of "institutional matrices" is offered, and the following groups of indicators should be distinguished: "private property institute"; "income institute"; "competition institute"; "hiring institute"; "exchange institute"; "financial market institute". To assess the institutional potential the system of indicators is offered. The indicators are divided into three groups: accounting ones (primary data statistics), assessment and analytical ones (calculated on the basis of primary data statistics), and point ones (on the basis of survey of enterprises’ managers). To assess the institutional potential the index method is used. The results of the research show that the institutes of financial market and institutes of exchange are more developed in the industrial regions while such indicators as the institutes of private property and institutes of income are much lower there. Therefore, even among the regions with high level of industrial development there are significant differences in the indicators by groups of the institutional potential. This indicates the inadvisability of developing and introducing a unique government policy of regional development and even a common policy on all industrial regions. The use of the above approach to the assessment of regions’ institutional potential in Ukraine allows establishing a list of indicators to calculate the region’s institutional potential and thus to come closer to the solution of a scientific and practical task of assessment of the institutional potential as a part of region’s economic potential as well as to form an idea about the institutional features of Ukraine’s regions. The calculation of the institutional potential index may be an element of typology of regions as a tool of regional analysis and policy of regional development. The identification of theoretical approaches to the development of the system of indicators of the group "institutes of development" and the creation of corresponding statistical base, as well the analysis of the role of culture and mentality features in the formation of the institutional potential of industrial regions can be one of the directions for further research.